Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Di BEI - Marchella Pindi, I Cenik Ardana (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to determine the significance of the effect of capital structure, profitability, firm size,investment decision and firm growth toward firm value at manufacturing company in Indonesia Stock Exchange in the period 2015-2017. The population used in this study were 69 manufacturing companies in 3 years period that was selected with purposive sampling method. Technique of data analysis using regression analysis with Fixed Effect Model using Eviews 9.0. The result of this research showed that capital structure and firm growth has negative effect and no significance toward firm value. Profitability and firm size has positive effect and significance toward firm value, while investment decisions has positive effect and no significance toward firm value